2021
DOI: 10.1017/bpp.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing default nudges: autonomy, manipulation, and choice-satisfaction as judged by people themselves

Abstract: Criticisms of nudging suggest that nudges infringe on decision makers’ autonomy. Yet, little empirical research has explored whether people who are subjected to nudges agree. In three between-group experiments (N = 2083), we subject participants to contrasting choice architectures and measure experiences of autonomy, choice-satisfaction, perceived threat to freedom of choice, and objection to the choice architecture. Participants who received a prosocial opt-out default nudge made more prosocial choices but di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Although nudges' effectiveness was originally thought to depend upon the nudgee being oblivious to their use (bovens, 2009), our findings show that nudges can still affect behaviour even when implemented by the nudgee themselves. These results are in line with recent findings that show that openness about the goal and mechanisms of nudging does not negate its effectiveness (bruns et al, 2018;cheung et al, 2019;Kroese et al, 2016;Loewenstein et al, 2015;Michaelsen et al, 2020;Michaelsen et al, 2021a;Paunov et al, 2019a;Paunov et al, 2019b;steffel et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although nudges' effectiveness was originally thought to depend upon the nudgee being oblivious to their use (bovens, 2009), our findings show that nudges can still affect behaviour even when implemented by the nudgee themselves. These results are in line with recent findings that show that openness about the goal and mechanisms of nudging does not negate its effectiveness (bruns et al, 2018;cheung et al, 2019;Kroese et al, 2016;Loewenstein et al, 2015;Michaelsen et al, 2020;Michaelsen et al, 2021a;Paunov et al, 2019a;Paunov et al, 2019b;steffel et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…It was even thought that resistance or reactance would result in counter effects (Brehm, 1989). Fortunately, empirical evidence is now accumulating that shows that transparency does not, in fact, hinder nudge effectiveness (Bang et al, 2020;Bruns et al, 2018;Cheung et al, 2019;Kroese et al, 2016;Loewenstein et al, 2015;Michaelsen et al, 2020;Michaelsen et al, 2021a;Steffel et al, 2016). Transparent nudges have even been found to be more effective than non-transparent nudges (e.g.…”
Section: The Ethics Of Nudgingmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, it yielded similar attitudes to those of the opt-in approach. Likewise, there is evidence that shows that default nudges may not be as manipulative and autonomy threatening as we feared (Michaelsen et al, 2021;Liu et al, 2022). Previous studies have shown that pro-self nudges are more popular than pro-social nudges (Hagman et al, 2015(Hagman et al, , 2022, while this result could vary depending on who does the nudging (Tannenbaum et al, 2017) and who is nudged (Jung and Mellers, 2016).…”
Section: Discussionmentioning
confidence: 84%